Upaya Penurunan Nyeri Pada Pasien Wound Dehiscence Post Disartikulasi HIP di RSOP. Dr. R. Soeharso - Pangestu, Lintang Hayu; , Arina Maliya, S. Kep. M.Si. Med (2016)
Pain is an unpleasant sensation and varies between individuals, one of nonpharmacological measures do nurses to reduce the level of pain a patient is by using deep breathing relaxation techniques whose effectiveness has not been clearly known. Deep breathing relaxation technique is a technique of doing a deep breath, slow breath and how to breathe in slowly This study aims to determine the effect of deep breathing to reduce pain scale on clients with medical diagnosis of wound dehiscence post hip disarticulation the ward Parang Kusumo RSOP Dr. R. Soeharso Surakarta. The method used was a case study, by performing the nursing care of patients wound dehischence post hip disarticulation ranging from assessment, intervention, implementation and evaluation of nursing. The results obtained after the 3x24-hour nursing care for the client with wound dehiscence post hip disarticulation with the problem of acute pain, physical mobility restrictions, body image disturbance, the risk of infection has been resolved partially and interventions should be continued. The influence nonpharmacological therapy in reducing pain scale, this is evidenced by the third day the pain scale was reduced from 5 to 3.